Mycobiota of Serrano Artisanal Cheese produced in Santa Catarina, Brazil - Pereira, Marcella Nunes; Silva, Juliana Regina da; Freire, Ítala Sabrina Fernandes; Escatolin, Lívia Colletti; Tallamini, Stéfano Caon (Revista de Ciências Agroveterinárias, 2019)
Serrano Artisanal Cheese is a native product from the South region of Brazil, produced by family labor from raw milk, which seeks to obtain its geographical indication. Many of the characteristics that particularize the types of cheese are given by its natural mycobiota. The objective of this study was to determine the fungal species present in 20 samples of Serrano Artisanal Cheese from four ripening periods (14, 21, 28, and 35 days), produced in October 2017, in Santa Catarina. Identification of molds was made by identification keys and yeasts by MALDI-TOF. The molds were isolated in 28 of the 80 samples and with various species, some being attributed to contamination. On the other hand, yeasts were detected in all samples, with some genera being more frequent, specially Kluyveromyces lactis, present in 27 samples, and some species of Candida spp. The identified species have already been isolated in other Brazilian artisanal cheeses produced in places with similar climate and relief to that of Serrano Artisanal Cheese.